Wildfowl at risk, 1992 - Green, Andy J (Wildfowl, 1965)
Brief accounts are given of the status and causes of decline of 50 species and subspecies of wildfowl (Anseriformes) that are known to be threatened with extinction. A number of changes are made to the earlier list presented in this journal by Kear and Williams (1978), and each taxon is assigned a provisional category of threat in line with recent proposals for the re-evaluation of IUCN categories made by Mace and Lande (1991).